Towards a socially just model: balancing hunger and response to the COVID-19 pandemic in Bangladesh - Rashid, Sabina Faiz; Theobald, Sally; Ozano, Kim (BMJ, 2022)
This article was published in BMJ Global Health [ © Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2020-002715 The Journal's website is at: https://gh.bmj.com/content/5/6/e002715.full